Requirement for Cyclic AMP/Protein Kinase A-Dependent Canonical NFκB Signaling in the Adjuvant Action of Cholera Toxin and Its Non-toxic Derivative mmCT - Terrinoni, Manuela; Holmgren, Jan; Lebens, Michael; Larena, Maximilian (Frontiers in Immunology, 2019)
Cholera toxin (CT) is widely used as an effective adjuvant in experimental immunology for inducing mucosal immune responses; yet its mechanisms of adjuvant action remain incompletely defined. Here, we demonstrate that mice lacking NFκB, compared to wild-type (WT) mice, had a 90% reduction in their systemic and mucosal immune responses to oral immunization with a model protein antigen [Ovalbumin (OVA)] given together with CT. Further, NFκB−/− mouse dendritic cells (DCs) stimulated in vitro with CT showed reduced expression of MHCII and co-stimulatory molecules, such as CD80 and CD86, as well as of IL-1β, and other pro-inflammatory cytokines compared to WT DCs. Using a human monocyte cell line THP1 with an NFκB activation reporter system, we show that CT induced NFκB signaling in human monocytes, and that inhibition of the cyclic AMP—protein kinase A (cAMP-PKA) pathway abrogated the activation and nuclear translocation of NFκB. In a human monocyte-CD4+ T cell co-culture system we further show that the strong Th17 response induced by CT treatment of monocytes was abolished by blocking the classical but not the alternative NFκB signaling pathway of monocytes. Our results indicate that activation of classical (canonical) NFκB pathway signaling in antigen-presenting cells (APCs) by CT is important for CT's adjuvant enhancement of Th17 responses. Similar findings were obtained using the almost completely detoxified mmCT mutant protein as adjuvant. Altogether, our results demonstrate that activation of the classical NFκB signal transduction pathway in APCs is important for the adjuvant action of both CT and mmCT.